Evaluation on Efficacy of Diagnostic Laparoscopy in the Diagnosis and Management of Chronic Abdominal Pain: A Teaching Hospital Based Study - Vishnu Kumar Sharma (Asian Journal of Medical Research, 2018)
Background: Chronic abdominal pain can be diagnostic challenge. These difficult patients are frequently seen by many different physicians and are subjected to myriad of tests without identifying the etiology of pain. Surgical consultation often occurs late after other modalities have failed to provide resolution of their symptoms. Subjects and Methods: This prospective study was conducted in the Department of Surgery, Varun Arjun Medical College & Rohilkhand Hospital, Banthra, Shahjahanpur, Uttar Pradesh, India. 45 Patients with chronic abdominal pain participate in this study. This study included patients presenting with history of nonspecific abdominal pain for 3 weeks or more who were admitted in surgical wards. Results: The most common site of pain was the periumbilical region (51.1%) followed by the right lower abdominal quadrant (23.3%). Twenty two patients were using either non-steroidal drugs or pain killers to relieve the pain, and five patients were using proton pump inhibitors. Fourteen patients (31.1%) had undergone at least one previous surgical abdominal procedure. All patient characteristics are summarised in table 3. The average length of the operative time was 54.09 minutes with the range from 32 to 116 minutes. There were no cases converted to open procedures. Out the 45 patients with chronic abdominal pain, a definitive diagnosis was established in 43 patients (95.5%), while no identifiable cause could be reached in two patients (4.4%). The most common laparoscopic findings were adhesions (77.8%). Other findings included appendiceal pathology (11.1%), hernia (2.2%), gall bladder pathology (2.2%), and mesenteric lymphadenopathy (2.2%). Table 2  summarises the laparoscopic diagnoses assigned to all patients. Laparoscopic management included adhesiolysis (35), appendectomy (5), hernia repair (1), cholecystectomy (1), and lymph node biopsy (1). Two patients had no interventions performed. Postoperative hospital stay ranged from two to twelve days with a mean of 3.8 days. Conclusion: In conclusion, Chronic abdominal pain of unknown origin represents a significant problem in surgical patients. Due to improvement in instrumentation and greater experience in the laparoscopy, the procedure no longer limited to visualization. This study showed that laparoscopy is an effective approach in the management of patients with chronic abdominal pain in whom conventional methods of investigations have failed to elicit a certain cause.